MODERN PEDAGOGICAL TECHNOLOGIES IN TEACHING HISTORY (American Journal of Interdisciplinary Research and Development, 2022)
Today, much attention is paid to the study of the history of independent Uzbekistan is focused. It is a way for the younger generation to learn more about our history opportunities to be proud of our history and draw conclusions offers.